Clinical practice teaching system for MNS cardiac rehabilitation: Delphi consensus - Caiyun Sun; Xingbin Du; Yanyan Fan; Guiyun Wang (PLoS ONE, 2026)
Background China faces a growing demand for cardiac rehabilitation professionals that outstrips available medical resources. While nursing master's candidates represent key talent reserves, current higher education lacks standardized training frameworks for cardiac rehabilitation nursing. This study developed a competency-based clinical training system through expert consensus to address this educational gap. Methods A modified two-round Delphi process engaged 22 cardiac rehabilitation experts. Initial expert feedback informed questionnaire refinement, followed by consensus-building analysis in the second round. Results The Delphi study demonstrated high engagement (100% Round 1; 96% Round 2 response rates) and acceptable expert authority (Cr = 0.83‑0.84). Kendall’s W values ranged from 0.13 to 0.21 (p < 0.05), indicating moderate agreement among experts. The consensus process yielded a structured framework of 5 domains, 29 subdomains, and 85 competency indicators. Conclusion The teaching system is scientifically valid, targeted, and practical, providing a comprehensive framework for training master's degree candidates in cardiac rehabilitation nursing.